Galleria mellonella as a consolidated in vivo model hosts: New developments in antibacterial strategies and novel drug testing - Marco Alfio Cutuli (Virulence, 2019)
A greater ethical conscience, new global rules and a modified perception of ethical consciousness entail a more rigorous control on utilizations of vertebrates for in vivo studies. To cope with this new scenario, numerous alternatives to rodents have been proposed. Among these, the greater wax moth Galleria mellonella had a preponderant role, especially in the microbiological field, as demonstrated by the growing number of recent scientific publications. The reasons for its success must be sought in its peculiar characteristics such as the innate immune response mechanisms and the ability to grow at a temperature of 37°C. This review aims to describe the most relevant features of G. mellonella in microbiology, highlighting the most recent and relevant research on antibacterial strategies, novel drug tests and toxicological studies. Although solutions for some limitations are required, G. mellonella has all the necessary host features to be a consolidated in vivo model host.